Desain dan Pembuatan Tungku Peleburan Logam Berbahan Bakar Gas Menggunakan Teknik Las Busur Logam Terlindung (SMAW) untuk Aplikasi Pengecoran Skala Kecil - Wisnu Murti; Sriyanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study presents the design, fabrication, and performance evaluation of a gas-fueled metal melting furnace developed using the Shielded Metal Arc Welding (SMAW) technique for small-scale foundries. The objective was to create an energy-efficient and environmentally friendly alternative to traditional solid-fuel furnaces commonly used in micro-industrial workshops. Fabrication employed locally available mild steel and refractory materials to ensure low production costs and accessibility. Experimental trials using aluminum revealed that the prototype achieved core melting temperatures above 900 °C and an average gas-to-metal ratio of 0.35 kg/kg, with potential optimization to 0.25 kg/kg. The furnace demonstrated approximately 22% thermal efficiency, exceeding conventional designs by 4%. Cleaner combustion reduced CO₂ emissions by 267 kg per ton of molten metal, while metallurgical tests indicated a 38% reduction in inclusion size and improved casting uniformity. The results confirm that SMAW-based fabrication can yield structurally reliable, cost-effective, and energy-efficient furnaces suitable for community-scale metal industries. The study supports sustainable industrial practices by promoting local manufacturing capabilities and aligning with energy transition goals.